Clinical Outcomes of Colonic Stent in a Tertiary Care Center - Mahesh Gajendran; Chandraprakash Umapathy; John Nasr; Andres Gelrud (Gastroenterology Research and Practice)
Introduction. Colonic obstruction is one of the manifestations of colon cancer for which self-expanding metal stents (SEMS) have been effectively used, to restore the luminal patency either for palliative care or as a bridge to resective surgery. The aim of our study is to evaluate the efficacy and safety of large diameter SEMS in patients with malignant colorectal obstruction. Methods and Results. A four-year retrospective review of the Medical Archival System was performed and identified 16 patients. The average age was 70.8 years, of which 56% were females. The most common cause of obstruction was colon cancer (9/16, 56%). Rectosigmoid was the main site of obstruction (9/16) and complete obstruction occurred in 31% of cases. The overall technical and clinical success rates were 100% and 87%, respectively. There were no immediate complications (<24 hours), but stent stenosis due to kinking occurred within one week of stent placement in 2 patients. Stent migration occurred in 2 patients at 34 and 91 days, respectively. There were no perforations or bleeding complications. Conclusion. Large diameter SEMS provide a safe method for palliation or as a bridge to therapy in patients with malignant colonic obstruction with high technical success and very low complication rates.